Ten years of "Optimal Therapy in Advanced Ovarian Cancer. Update" Meeting. (1st February 2008) - Poveda, A.
Abstract : The International Symposium on Advanced Ovarian Cancer: Optimal Therapy was founded by Dr. Andrés Poveda and Prof. Jan B. Vermorken, and each edition has been directed by them. The 6th edition was held on March 2, 2007. This symposium is organized every other year by GEICO (Grupo Español de Investigación de Cáncer de Ovario/Spanish Ovarian Cancer Research Group), under the auspices of the Spanish Society of Medical Oncology (SEOM), the Gynecologic Cancer Intergroup (GCIG), and the European Society of Medical Oncology (ESMO) Educational Committee for its Medical Oncology Recertification Approval (ESMO/MORA) Program. One hundred and fifty people attended the symposium's 1st edition, held in 1996. Since then, the interest in this meeting has increased. Last year, almost three hundred people coming not only from Spain but also from Europe, North and Latin America, Asia, and Australia were present in the symposium. This is a great challenge for us. Some important international cooperative groups from Europe, America, and Australia collaborate with this symposium, such as GOG, NCIC, EORTC, AGO, Scottish Group, ICON, GINECO, NSGO, ANZGOG, and others.